2015
DOI: 10.1093/cercor/bhv225
|View full text |Cite
|
Sign up to set email alerts
|

Two New Cytoarchitectonic Areas on the Human Mid-Fusiform Gyrus

Abstract: Areas of the fusiform gyrus (FG) within human ventral temporal cortex (VTC) process high-level visual information associated with faces, limbs, words, and places. Since classical cytoarchitectonic maps do not adequately reflect the functional and structural heterogeneity of the VTC, we studied the cytoarchitectonic segregation in a region, which is rostral to the recently identified cytoarchitectonic areas FG1 and FG2. Using an observer-independent and statistically testable parcellation method, we identify 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
136
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 92 publications
(147 citation statements)
references
References 74 publications
10
136
1
Order By: Relevance
“…The anterior portion of the basal temporal dark cluster, which comprises the areas 175 and 176 of our map (Fig. 6), clearly corresponds with the cytoarchitectonic area 20tc of Sarkissov et al (1955); the posterior part of this cluster, which includes the areas 173, 174, 177, 179 and 180 of our map, roughly corresponds with the cytoarchitectonic areas FG3 and FG4, recently described by Lorenz et al (2015). …”
Section: Discussionsupporting
confidence: 82%
“…The anterior portion of the basal temporal dark cluster, which comprises the areas 175 and 176 of our map (Fig. 6), clearly corresponds with the cytoarchitectonic area 20tc of Sarkissov et al (1955); the posterior part of this cluster, which includes the areas 173, 174, 177, 179 and 180 of our map, roughly corresponds with the cytoarchitectonic areas FG3 and FG4, recently described by Lorenz et al (2015). …”
Section: Discussionsupporting
confidence: 82%
“…These results provide evidence that regions which appear homogenous in terms of their category-selectivity (Tsao et al, 2006), but are anatomically and cytoarchitectonically distinct (Caspers et al, 2013; Grill-Spector and Weiner, 2014; Lorenz et al, 2015), differ in how they respond to a stimulus over time and in their potential contribution to ongoing visual perception.…”
Section: Discussionmentioning
confidence: 71%
“…Two additional posterior fusiform electrodes, located medial to the mid-fusiform sulcus, were also object-selective and duration-tracking, however their selectivity was limited to the onset response, that is, the response to faces and objects did not differ in the late (1200–1500 ms) time window. The locations of the two face-selective electrodes correspond to the posterior fusiform face-selective region pFus-faces (or FFA-1, Grill-Spector and Weiner, 2014), and to cytoarchitectonic region FG2 (Caspers et al, 2013), suggesting a functional distinction between this region and the more anterior mFus-faces region (FFA-2, related to cytoarchitectonic area FG4, Lorenz et al, 2015), which showed high category selectivity but little duration-tracking.…”
Section: Resultsmentioning
confidence: 97%
“…Details on the cytoarchitectonic regions referred to in the results tables may be found in the following publications reporting on Broca’s region (Amunts et al, 1999), motor cortex (Geyer et al, 1996), somatosensory cortex (Geyer, Schleicher, & Zilles, 1999; Grefkes, Geyer, Schormann, Roland, & Zilles, 2001), amygdala and hippocampus (Amunts et al, 2005), visual cortex (Amunts, Malikovic, Mohlberg, Schormann, & Zilles, 2000), lateral occipital and ventral extrastriate cortex (Malikovic et al, 2015; Rottschy et al, 2007), cerebellum (Diedrichsen, Balsters, Flavell, Cussans, & Ramnani, 2009), posterior fusiform gyrus (J. Caspers et al, 2013), mid-fusiform gyrus (Lorenz et al, 2015), basal forebrain (Zaborszky et al, 2008) and thalamus (connectivity-based regions: Behrens et al, 2003). …”
Section: Methodsmentioning
confidence: 99%